(untitled) (International journal of artificial intelligence, 2024)
Blood is a specialized connective tissue that plays a critical role in maintaining physiological homeostasis. This article explores the composition, functions, and physiology of blood, including plasma, red blood cells, white blood cells, and platelets. Blood is essential for transport, regulation, and protection within the body. Its functions include oxygen and carbon dioxide transport, nutrient delivery, immune defense, and blood clotting. Additionally, the roles of red blood cells in gas exchange, white blood cells in immunity, and platelets in hemostasis are highlighted. Blood-related disorders such as anemia, leukemia, and hemophilia are also discussed.